The Development Modern Chinese Dance Skills and Perceptions Using Task-based Teaching Method for students of Guangxi Polytechnic and Vocational Technical College in China - Minghui, Wang; Bhothisarn , Phitorn (วารสารวิทยาลัยนครราชสีมา สาขามนุษยศาสตร์และสังคมศาสตร์, 2026)
The purposes of this research were to (1) to compare students’ modern Chinese dance skills before and after the implementation of task-based teaching, and (2) to examine students’ perceptions toward task-based learning in modern Chinese dance instruction. The sample group used in this study was one class, 30 of Guangxi Polytechnic and Vocational Technical College students which was conducted by cluster random sampling. The research design was one-group pretest posttest design. The research instruments included (1) Task-based teaching method lesson plans which has the mean of experts’ assessment at the highest level (2) Dance performance assessment test with the mean of experts’ assessment at 4.80, is appropriate at the highest level and (3) Students’ perception questionnaire of a five-point Likert scale, which had the value of reliability at 0.86. The finding were as follow, The post-test of modern Chinese Dance skills by using Task-based teaching method was higher than pretest with statistically significant at 0.05 level and the students’ perception on modern Chinese Dance skills by using Task-based teaching method was at the most level in total ( = 4.53, S.D.=0.62).